Grafted Natural Polymer as New Drag Reducing Agent: An Experimental Approach - Abdulbari, Hayder A.; Siti Nuraffini, Kamarulizam; Nour, A. H. (CI & CEQ, 2012)
The present investigation introduces a new natural drag reducing agent which has the ability to improve the flow in pipelines carrying aqueous or hydrocarbon liquids in turbulent flow. Okra (Abelmoschus esculentus) mucilage drag reduction performance was tested in water and hydrocarbon (gas-oil) media after grafting. The drag reduction test was conducted in a buildup closed loop liquid circulation system consisting of two pipes of inside diameters (ID) 0.0127 and 0.0381 m, four testing sections in each pipe (0.5 to 2.0 m), tank, pump and pressure transmitters. Reynolds number (Re), additive concentration and the transported media type (water and gas-oil), were the major drag reduction variables investigated. The experimental results show that new additive drag reduction ability is high, with maximum achieved percentage of drag reduction (%Dr) up to 60%. The experimental results showed that the drag reduction ability increased by increasing the additive concentration. The %Dr was found to increase by increasing Re by using the water-soluble additive while it was found to decrease by increasing Re when using the oil-soluble additive. The %Dr was higher in the 0.0381 m ID pipe. Finally, the grafted and natural mucilage showed high resistance to shear forces when circulated continuously for 200 s in the closed-loop system.